2021
DOI: 10.3390/jcm11010232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antipsychotic Treatment on Neutrophil-to-Lymphocyte Ratio during Hospitalization for Acute Psychosis in the Course of Schizophrenia—A Cross-Sectional Retrospective Study

Abstract: Background: Studies have shown that there are deviations in the results of peripheral blood counts, which lead to increased values of the neutrophils-to-lymphocytes ratio (NLR) in schizophrenia. Antipsychotic drugs have proven to lower the levels of pro-inflammatory cytokines and a growing number of studies indicate a similar effect on NLR values. Methods: We identified inpatients with schizophrenia and collected data of NLR at the beginning (NLR1) and end (NLR2) of hospitalization, the status of antipsychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…Additionally, there was a negative correlation between chlorpromazine equivalent doses and baseline positive symptoms (r=-0.256, P = 0.033). However, chlorpromazine equivalent doses did not correlate with systemic in ammatory biomarkers in our study (all P > 0.05), which is inconsistent with previous studies showing that antipsychotics may reduce NLR results 39,40 . Although a large retrospective study revealed a negative relationship between NLR and BPRS negative symptom scores in the antipsychotic treatment group 34 , We did not nd any systemic in ammatory biomarkers associated with negative symptoms, suggesting elevated NLR may not necessarily correlated with the severity of the illness.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, there was a negative correlation between chlorpromazine equivalent doses and baseline positive symptoms (r=-0.256, P = 0.033). However, chlorpromazine equivalent doses did not correlate with systemic in ammatory biomarkers in our study (all P > 0.05), which is inconsistent with previous studies showing that antipsychotics may reduce NLR results 39,40 . Although a large retrospective study revealed a negative relationship between NLR and BPRS negative symptom scores in the antipsychotic treatment group 34 , We did not nd any systemic in ammatory biomarkers associated with negative symptoms, suggesting elevated NLR may not necessarily correlated with the severity of the illness.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, NLR has been proposed as a biomarker for schizophrenia and even for other neurodegenerative diseases ( 23 ). This is also ratified by this study since the age of symptom onset correlated positively and significantly with NLR, data already reported by other authors, which has been interpreted as indicative of a chronic inflammatory state both in schizophrenia and in bipolar disorder, so it could potentially be used as an indicator of the evolution of psychosis symptoms ( 24 , 25 ).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, a retrospective analysis revealed elevated peripheral and/or cerebrospinal fluid IL-6 levels in schizophrenic patients [ 112 ]; however, there are also reports of reduced production of this cytokine [ 8 ]. Simultaneously, other research does not find a strict positive correlation between the severity of positive symptoms, cognitive deficits and enhanced levels of proinflammatory cytokines, such as IL-6, IL-1β and TNF-α [ 113 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%